Bibliometric and Systematic Review of Development-Oriented Zakat Management in Depok City, Indonesia - Ade Nur Rohim; Lili Puspita Sari; Kevin Shaquille Lesmana; Ilham Alivian (Islamiconomic : Jurnal Ekonomi Islam, 2025)
This study maps and analyzes research trends on zakat management in Depok City, Indonesia, and examines its contribution to local development from 2020 to 2024. Forty relevant articles identified through Google Scholar using the Publish or Perish tool were analyzed with VOSviewer software. The findings reveal four main thematic clusters: studies on Baznas of Depok City as an institutional entity, zakat management practices, determinants of zakat payment behavior, and Amil Zakat Institutions (LAZ). Most research focuses on the distribution of zakat funds for empowerment-oriented economic programs. The trend analysis shows fluctuating research activity, peaking in 2022 and declining thereafter, with contributors affiliated with both Islamic and general higher education institutions. The novelty of this study lies in its localized bibliometric approach, which systematically captures the intellectual structure of zakat research at the city level—an area rarely explored in prior literature. Its scholarly significance lies in advancing understanding of how local zakat governance contributes to sustainable community development. Practically, it offers evidence-based insights for policymakers to strengthen institutional performance and diversify productive zakat programs. The study’s limitation lies in its reliance on Google Scholar data, suggesting the need for broader database coverage in future research.